Developing Web-based Learning Media ‘Geopedia’ Using SAM Model - Amin, Saiful; Kurniawan, Muchammad Akbar; Putra, Muhammad Akmal Muzakki Dwi Syah; Indriansyah, Renata Tiand (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3177, 2024)
Web-based learning media is important to develop in order to improve the quality of learning. This research aims to develop Geopedia web media in geography lessons in high school using the Successive Approximation Model (SAM). The development of Geopedia web media in this study used the SAM 1 model with its stages, namely 1) evaluate, 2) design, and develop. Data analysis methods are qualitative descriptive analysis and quantitative descriptive analysis. Qualitative descriptive analysis collected data on reviews and recommendations given by Geography material experts, media experts, teachers, and students. Quantitative analysis in the form of percentage values obtained from the analysis of criteria scores with a Likert scale. Based on the results of the study, the development product in the form of web learning is suitable for use in learning Geography, especially Lithosphere. The feasibility value of the material expert is 91.25%. Then from media experts is 93.33%. Then, the feasibility value from students is 88.44% and the teacher is 88.27%. Therefore, the average feasibility value of this web learning is 91.25%, including in the very effective category.